The Warship Schleswig-Holstein: History, Cultural Value and Legal Status - Maili Roio (Journal of Ethnology and Folkloristics)
The current paper looks into the issues connected with underwater cultural heritage in Estonia and deals with its legal and physical protection. The report discusses the topic of what we actually mean by underwater heritage, what are the threats in terms of preservation and what are the possibilities to protect underwater heritage in Estonia. The paper analyses objects that are not defined by the UNESCO convention from 2001 as underwater cultural heritage, but which form a considerable part of underwater objects in Estonia that are protected by the state. A wide range of challenges – protection, ownership, value – is illustrated by the study of the history and present state of the battleship Schleswig-Holstein.